A New Species of the Genus Hemicorallium (Cnidaria: Octocorallia: Scleralcyonacea: Coralliidae) Collected from Okinawa Island - Masanori Nonaka; Kenji Takata; Nina Yasuda (Species Diversity)
Herein, we describe a new species in the genus Hemicorallium Gray, 1867 (Coralliidae), H. ryukyuense sp. nov. An almost complete colony was found at a depth of 860 m approximately 10 km east of Okinawa Island. The colony was identified through the visual and microscopic observations of standard morphological characteristics, including colony size, the diameters of colony base and branches, the diameter and height of autozooid mounds, coenenchyme thickness, and sclerite sizes. The specimen is characterized by large autozooid mounds (1.1–2.0 mm in diameter) and a pinkish-to-reddish cortex and axis. A distinctive feature of this specimen is the absence of commensal burrows on the axis. This is the first described species of precious coral with the Ryukyu Islands as its type locality. Pairwise genetic distances indicate that H. ryukyuense constitutes a distinct evolutionary lineage. However, tree topologies differed among loci, and the interspecific distances within Hemicorallium were smaller than the divergence observed between Pleurocorallium elatius (Ridley, 1882) and P. konojoi (Kishinouye, 1903). Consequently, population-level genomic data will be needed to confirm the species status of H. ryukyuense with greater confidence.